Pengaruh Media Aplikasi Let's Read Asia terhadap Keterampilan Berbicara Siswa Kelas 5 - Arina Esfanti; Muhammad Misbahul Munir (JANACITTA, 2026)
Abstract This study aims to determine the effect of 5th grade students' speaking skills on Indonesian subjects at SDN 2 Sowan Lor Jepara using Let's Read Asia learning media. The research design used is a quantitative approach using a pre-experimental research design in the form of One Group Pretest-Posttest Design, the sample used was 27 students. The research instrument used was a direct oral test to students. The results of the descriptive analysis showed an increase in the average pre-test score (9.8889) to post-test (14.8148) and a decrease in the standard deviation (from 2.51661 to 1.88184), the paired sample t-test produced a significance value of 0.000 (p <0.05), indicating a significant difference between the pre-test and post-test. The level of influence of this application is in the medium category with an average N-Gain value of 0.4979, supported by a standard deviation of 0.12696 which indicates a not too large variation in improvement between students. The effectiveness of the Let's Read Asia application is based on its ability to increase reading interest through the provision of free picture stories, translation features that expand the collection, and its positive influence on the classroom atmosphere that encourages student activity, curiosity, and learning motivation, especially in terms of speaking skills. These results strengthen the evidence that Let's Read Asia is a useful learning tool. Abstrak Penelitian ini bertujuan untuk mengetahui pengaruh keterampilan berbicara siswa kelas 5 pada mata pelajaran Bahasa Indonesia di SDN 2 Sowan Lor Jepara menggunakan media pembelajaran Let’s Read Asia. Desain penelitian yang digunakan adalah pendekatan kuantitatif dengan menggunakan desain penelitian pra-eksperimental dalam bentuk One Grup Pretest-Posttest Design, sampel yang digunakan berjumlah 27 siswa. Instrumen penelitian yang digunakan yakni tes lisan secara langsung kepada siswa. Hasil analisis deskriptif menunjukkan peningkatan nilai rata-rata pre-test (9.8889) menjadi post-test (14.8148) dan penurunan standar deviasi (dari 2.51661 menjadi 1.88184), Uji paired sample t-test menghasilkan nilai signifikansi 0.000 (p < 0.05), menunjukkan adanya perbedaan signifikan antara pre-test dan post-test. Tingkat pengaruh aplikasi ini berada pada kategori sedang dengan nilai N-Gain rata-rata 0.4979, didukung oleh standar deviasi 0.12696 yang menunjukkan variasi peningkatan yang tidak terlalu besar antar siswa. Efektivitas aplikasi Let’s Read Asia didasarkan pada kemampuannya untuk meningkatkan minat baca melalui penyediaan cerita bergambar gratis, fitur penerjemahan yang memperluas koleksi, serta pengaruh positifnya terhadap suasana kelas yang mendorong keaktifan, rasa ingin tahu, dan motivasi belajar siswa, terutama dalam hal keterampilan berbicara. Hasil ini menguatkan bukti bahwa Let’s Read Asia merupakan alat bantu pembelajaran yang bermanfaat.